Effect of ankle dorsiflexion on displacement and strain in the tibial nerve and biceps femoris muscle at the posterior knee during the straight leg raise: Investigation of specificity of nerve movement - Bueno-Gracia, Elena; Estébanez-de-Miguel, Elena; López-de-Celis, Carlos; Shacklock, Michael; Caudevilla-Polo, Santos; González-Rueda, Vanesa; Pérez-Bellmunt, Albert (Clinical biomechanics (Bristol), 2020)
A structural differentiation maneuver has been proposed to differentiate between muscle and nerve involvement during the straight leg raise test. However, to date, the mechanical specificity of this maneuver for the tibial nerve at the posterior knee has not been tested. The aim of this study was to investigate the specificity of ankle dorsiflexion as a differentiation maneuver between the tibial nerve and the biceps femoris muscle at the posterior knee during the straight leg raise in cadavers. A cross-sectional study was carried out. In fresh frozen cadavers, with microstrain devices and Vernier calipers, strain and excursion in the tibial nerve and distal biceps femoris muscle were measured during ankle dorsiflexion at 0°, 30°, 60° and 90° of hip flexion of the straight leg raise. Ankle dorsiflexion resulted in significant distal excursion and increased strain in the tibial nerve (p < 0.05) whilst the muscle was not affected by the dorsiflexion (p > 0.05) at all hip flexion angles. Ankle dorsiflexion was mechanically specific between the tibial nerve and biceps femoris during the straight leg raise. This study adds to evidence that, in certain circumstances, dorsiflexion may be used in differentiation of nerve and muscle disorders in the posterior knee. •Ankle dorsiflexion increases the strain in the tibial nerve.•Ankle dorsiflexion produces distal sliding of the tibial nerve.•Ankle dorsiflexion does not affect the biceps femoris.